2015
DOI: 10.1186/s12916-015-0433-1
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic health expenditure and 12-month mortality associated with cancer in Southeast Asia: results from a longitudinal study in eight countries

Abstract: BackgroundOne of the biggest obstacles to developing policies in cancer care in Southeast Asia is lack of reliable data on disease burden and economic consequences. In 2012, we instigated a study of new cancer patients in the Association of Southeast Asian Nations (ASEAN) region – the Asean CosTs In ONcology (ACTION) study – to assess the economic impact of cancer.MethodsThe ACTION study is a prospective longitudinal study of 9,513 consecutively recruited adult patients with an initial diagnosis of cancer. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
83
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 31 publications
10
83
2
Order By: Relevance
“…As we can see from the results, increased length of stay, no insurance, low level of education, more people in family, high OOP%, household with at least one person over 65 years of age and low‐income level, these factors had major impact on CHE. When CHE was defined as OOP medical costs exceeding 30% of annual household income by some researchers, it was found that education background, income level, type of health institutions, and health insurance were influencing factors of CHE in the study on influencing factors of CHE among households with cancer in 10 countries in southeast Asia, of which the results are similar to ours 8. Also, the study found that cancer stage was one of the factors—the further the stage extended, the more likely CHE would occur.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As we can see from the results, increased length of stay, no insurance, low level of education, more people in family, high OOP%, household with at least one person over 65 years of age and low‐income level, these factors had major impact on CHE. When CHE was defined as OOP medical costs exceeding 30% of annual household income by some researchers, it was found that education background, income level, type of health institutions, and health insurance were influencing factors of CHE in the study on influencing factors of CHE among households with cancer in 10 countries in southeast Asia, of which the results are similar to ours 8. Also, the study found that cancer stage was one of the factors—the further the stage extended, the more likely CHE would occur.…”
Section: Discussionsupporting
confidence: 83%
“…A study conducted in South Korea by Choi et al7 showed that 39.8% of the 211 cancer patients suffered from CHE. While in South Asia, 48% of the 9513 patients with cancer experienced CHE 8. It also showed that the incidence of CHE varied among different countries.…”
Section: Introductionmentioning
confidence: 97%
“…The ACTION study reported that, a year after diagnosis, only 23% of cancer patients from eight countries in ASEAN were alive with no financial catastrophe [15]. A study in Haiti found that two-thirds of women with breast cancer were to face financial catastrophe because of the treatment costs [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, only older age, lower income, and receiving multiple treatment methods were shown to be statistically significant correlates of the impoverishment problem. At regional level, the ACTION study found that having a below-average income, having no health insurance, not having paid work, and having attended not higher than primary education were all associated with higher odds of experiencing catastrophic expenditure [15] and this reinforces the current knowledge of relationship between socioeconomically disadvantaged conditions and higher risks of financial hardship [23]. There should be financial support programs to cover the treatment costs of cancer and to help socioeconomically disadvantaged cancer patients to cope with the challenging situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation